Pengaruh Kualitas Sistem Informasi Penjualan Terhadap Tingkat Kepuasan Pelanggan Di Toko Afifah Fruits - Rhamadani, Anggy; Pratiwi, Ika Ayu; Yeni, Hari (CV. SINAR HOWUHOWU, 2026)
This study aims to examine and empirically verify the effect decales information system quality on customer satisfaction at Afifah Fruits Store. Along with the transition from conventional management practices digital systems, Afifah Fruits Store has implemented Point of Sales (POS) and Quick Response de Indonesian Standard (QRIS) technologies to enhance transaction efficiency. This research employs a quantitative approach using a survey method by distributing questionnaires to customers of Afifah Fruits Store. The sampling technique applied in the study is purposive sampling. Data analysis is conducted using simple linear regression to determine the extent to which the quality of the information system influences customer satisfaction. The findings are expected to indicate that the quality the sales information system, including ease of use, reliability, and access speed, has a positive and significant effect on customer satisfact Practically, this study provides recommendations for MSME practitioners to optimize the use of information te nology as a strategic effort to improve service quality and strengthen customer loyalty in the digital era.